Broad perspectives in understanding vaccine hesitancy and vaccine confidence: an introduction to the special issue. - Baldwin, Austin S.; Tiro, Jasmin A.; Zimet, Gregory D. (Journal of Behavioral Medicine, 2023)
The World Health Organization has designated vaccine hesitancy and vaccine confidence among the most pressing issues in global health. The COVID-19 pandemic has made vaccine hesitancy and vaccine confidence particularly salient and urgent. The purpose of this special issue is to highlight a broad range of perspectives on these critical issues. We have included a total of 30 papers that address issues related to vaccine hesitancy and vaccine confidence across multiple levels of the Socio-Ecological Model. We have organized the empirical papers into the following sections: individual-level beliefs, minority health and health disparities, social media and conspiracy beliefs, and interventions. In addition to the empirical papers, three commentaries are included in this special issue.